2020
DOI: 10.1126/sciadv.aay2387
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic preconditioning in perfusion bioreactors improves vascularization and bone formation by human bone marrow aspirates

Abstract: Cell-derived extracellular matrix (ECM) provides a niche to promote osteogenic differentiation, cell adhesion, survival, and trophic factor secretion. To determine whether osteogenic preconditioning would improve the bone-forming potential of unfractionated bone marrow aspirate (BMA), we perfused cells on ECM-coated scaffolds to generate naïve and preconditioned constructs, respectively. The composition of cells selected from BMA was distinct on each scaffold. Naïve constructs exhibited robust proangiogenic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…Both bone formation and regeneration of blood vessels ensure the success of implanted metallic devices, in terms of osseointegration and angiogenic functional recovery [66]. The presence of MSCs and ECs at the site of injury play key roles in osteogenic graft integration, enhanced infiltration of these cells ensuring early vascularization and bone formation [76]. The ability of dip-coated blend coatings to establish optimal interactions with both MSCs and ECs was herein demonstrated.…”
Section: Biocompatibility Of Pcl-blend-peg Coatingsmentioning
confidence: 85%
“…Both bone formation and regeneration of blood vessels ensure the success of implanted metallic devices, in terms of osseointegration and angiogenic functional recovery [66]. The presence of MSCs and ECs at the site of injury play key roles in osteogenic graft integration, enhanced infiltration of these cells ensuring early vascularization and bone formation [76]. The ability of dip-coated blend coatings to establish optimal interactions with both MSCs and ECs was herein demonstrated.…”
Section: Biocompatibility Of Pcl-blend-peg Coatingsmentioning
confidence: 85%
“…Anti-sclerostin antibody is a new option for bone formation, and further clinical investigations are needed to evaluate its benefits and risks (24). In recent years, anabolic therapeutic strategies for pathological bone loss have attracted attention (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The first step was to optimize hMSC seeding on 3D hybrid scaffolds. Whereas some authors carried out cell seeding in static conditions and then moved cell/scaffold construction inside the bioreactor for dynamic culture [ 46 , 47 , 48 , 49 ], others studies implemented dynamic conditions for cell seeding and culture [ 30 , 50 , 51 ]. Static cell seeding is by far the most commonly used seeding method but it provides low seeding efficiencies and non-uniform cell distribution [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo studies also demonstrated that MSC preconditioning in bioreactor prior to implantation enhanced in vivo results as quantity and quality of new bone [ 23 , 28 , 29 ]. A more recent work demonstrated that bioreactor-based preconditioning augments the bone-forming potential of human bone marrow aspirates [ 30 ].…”
Section: Introductionmentioning
confidence: 99%